VIRGIN COCONUT OIL MEMPERCEPAT PENYEMBUHAN LUKA PERINEUM DI PUSKESMAS RAWAT INAP KOTA DENPASAR - Ni Nyoman Sumiasih (Poltekkes Kemenkes Denpasar, 2017)
Jurusan Kebidanan Politeknik Kesehatan Denpasar sumiasih.ninyoman@gmail.comAbstract. One means to speed up the perineal tear healing is by the application of virgin coconut oil (VCO) that have efficacy to accelerate wound healing. This study aims to find differences in healing of the perineum tear treated to the normal delivery care added with VCO. This research was conducted in Puskesmas Denpasar from June to early to October 2015. The type of research is experimental design with post test only control, with a time series approach. The study population was postpartum mothers who gave birth in Puskesmas Denpasar who suffered level II lacerations. The sample of the control group are 16 people who were treated to the standard normal delivery , and the treatment group are 16 people who were treated with the addition of Virgin Coconut Oil (VCO).Average time of tear recovery in the control group took 6 to 8 days whilst in the treatment group it took 4 to 5 days. The differences of healing in the control and treatment groups were analyzed using the Mann-Whitney statistical test, with results showing that healing treatment groups is faster than the control groups. Therefore it could be concluded that perineal tear healing treated to the standard normal delivery care added with VCO is faster than those treated only to the standard normal delivery care.It is suggested to all health care practitioners who serve women with perineal laceration to give treatment to the standard normal delivery care added with VCO to speed up healing.KeyKeywords: perineal tear, standard normal delivery care, virgin coconut oil. ABSTRAK. Untuk mempercepat penyembuhan luka perineum ini,virgin coconut oil(VCO) memiliki khasiat mempercepat penyembuhan luka. Penelitian ini bertujuan untuk menemukan perbedaan penyembuhan luka perineum yang dirawat sesuai asuhan persalinan normal (APN) dengan ditambah VCO. Penelitian ini dilakukan di Puskesmas Rawat Inap Kota Denpasar dari bulan Juni sampai awal Oktober 2015. Jenis penelitian adalah eksperimental designpost test only control group dengan pendekatan time series. Populasi penelitian ini ibu nifas melahirkan di Puskesmas Rawat Inap Kota Denpasar yang mengalami laserasi tingkat II, dengan sampel 16 orang kelompok kontrol dirawat sesuai APN, dan 16 orang kelompok perlakuan dirawat sesuai APN ditambah VCO.Rata-rata penyembuhan luka pada kelompok kontrol 6 sampai 8 hari sedangkan pada kelompok perlakuan 4 sampi 5 hari. Perbedaan penyembuhan kelompok kontrol dan perlakuan dianalisis dengan uji statistic Mann Whitney Test, hasilnya penyembuhan kelompok perlakuan lebi cepat daripada kelompok kontrol. Dapat disimpulkan penyembuhan luka perineum yang dirawat sesuai standar APN ditambah VCO lebih cepat dibandingkan dengan yang dirawat sesuai standar APN.Disarankan kepada semua praktisi kesehatan yang melayani perempuan dengan laserasi perineum merawat sesuai APN ditambahkan dengan VCO untuk mempercepat penyembuhan.Kata Kunci: luka perineum, Standar Asuhan persalinan normal, vco